Burnout Syndrome in COVID-19: an analysis of physicians from the public and private health system in the state of Sergipe (Research, Society and Development, 2022)
Objective: To compare the incidence of Burnout Syndrome (BS) among public and private physicians in Sergipe- Brazil, during the fight against COVID-19, investigating the relevance of the public and private work environment in the development of the disease. Methodology: Analytical study of a quantitative, cross-sectional nature, involving 86 doctors working directly with COVID-19 in Sergipe. An online, self-administered, objective and anonymous questionnaire was used, with questions composed by the Maslach Burnout Inventory. The positivity of the syndrome was compared among physicians from the public, private and both services, evaluating the prevalence of the three dimensions of BS in each one. Pearson chi-square, Shapiro-Wilks and Kruskal-Wallis tests were used. Results: 81.5% of those working in public service were positive for Burnout, compared to 33.3% in private sector. In the public sector, there was a predominance of high levels of emotional exhaustion (14.8%) and cynicism (14.8%). The lowest rates of emotional exhaustion (47.6%), cynicism (90.5%) and the highest rates of work effectiveness (85.7%) were in private service. In the analysis of odds ratio, exclusive performance in private hospitals decreased chances of BS, in relation to public hospitals. Conclusion: There was a predominance of BS in public service workers and exclusive performance in private hospitals decreased chances of BS, contributing to the hypothesis that public service is a determining factor in the development of the syndrome. To prevent and intervene in the illness of physicians, it is necessary to transform the current Brazilian public health reality and, thus, the work environment of these professionals.